Let's play design - Farivarsadri, Guita; Alsac, Ustun (Open House Int, 2006)
Teaching design through learning by doing is still the dominant form of architectural education as it is believed that the skills, the language and the approach to problems of design con be learned more effectively through direct experience rather than through other means. That is why architecture students have to repeat design studio courses until they reach a certain level of experience. Design, especially the work done in design studios, has many similarities with ploy. Generally the subjects ore imaginary. The designs are presented using models trying to simulate real-life situations. And it has some fixed rules. Actually there is very little difference between a girl playing with a doll, a boy with toy trucks and on architecture student working on a design project. All of them deal with simulations, role-playing, preparing themselves for real-life situations. We hove observed that students learn more about design when they approach it in a playful manner. When they do this they also enjoy what they do. But this kind of education needs planning and preparation if it is going to yield good results. This article attempts to discuss about the benefits of planning a design studio as a kind of ploy activity by giving some examples from our experiments and observations we hove been conducting at our university.
Keywords: play; game; design; design education; architectural education